Listing Effect in Acquirer Returns and Economic Growth Uncertainty in the Target Country: The Case of Cross-border M&A from Emerging Economies. Issue 2 (26th January 2021) - Kim, Byoung-Jin; Jung, Jin-Young; Cho, Sung-Woo
ABSTRACT: We empirically prove that the negative listing effect of mergers and acquisitions (M&A) is more pronounced in target countries with high gross domestic product (GDP) growth rate uncertainty than in countries without such uncertainty. We examine a sample of 343 non-financial firms that disclosed cross-border M&A between 2000 and 2019 in the Korea Exchange stock market and 49 countries where the target firms are located. We show that the listing effect caused by economic growth uncertainty in the target country is stronger for cross-border M&A during the global financial crisis or when the target firms are based in emerging countries.